2019
DOI: 10.21470/1678-9741-2017-0209
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Acute Kidney Injury after Isolated CABG Surgery: a Prospective Cohort Study

Abstract: Background Acute kidney injury (AKI) is a frequent event after cardiac surgery with increased mortality and morbidity. We explored frequency, risk factors, and associated morbidity and mortality of AKI after isolated coronary artery bypass grafting (CABG) surgery at a single institution. Methods All consecutive adults undergoing CABG surgery from March 2013 to October 2016 were assessed for development and severity of AKI based on Acute Kidney Injury Network (AKIN) crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
3
26
1
Order By: Relevance
“…Despite the potential negative impact of opium addiction in patients undergoing CABG surgery, some studies suggest protective effects of opium abuse as a protective factors in these patients. In a study by Amini et al has shown that patients with opium abuse after CABG had significantly less frequent of acute kidney injury compared to non-opium abusers [ 40 ]. Also, Maghsoudi et al reported that the length of inotropic agents in CABG perioperative period was significantly lower in opium addicted compared to non-opium dependent patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential negative impact of opium addiction in patients undergoing CABG surgery, some studies suggest protective effects of opium abuse as a protective factors in these patients. In a study by Amini et al has shown that patients with opium abuse after CABG had significantly less frequent of acute kidney injury compared to non-opium abusers [ 40 ]. Also, Maghsoudi et al reported that the length of inotropic agents in CABG perioperative period was significantly lower in opium addicted compared to non-opium dependent patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Transfusion in low-risk patients has been associated with an 8-to 10-fold increase in adverse outcomes 21 and has been associated with AKI in cardiac surgical patients. 22,23 We found reduced AKI in patients refusing transfusion and no difference in morbidity or mortality. Furthermore, a recent publication found no additional cost associated with refusal of transfusion in cardiac surgery.…”
Section: Discussionmentioning
confidence: 72%
“…neutrophils, and different biochemical pathways may result in microthrombosis, microemboli and depletion of coagulation factors [22]. These factors contribute to tissue injury and endothelial dysfunction, to predisposing patients to organ injury and to increasing perivascular edema [22, 27]. Renal dysfunction can be a common complication after coronary artery bypass surgery with use of heart-lung machine [4, 9].…”
Section: Discussionmentioning
confidence: 99%